Early Outcome of Intra Peritoneal Onlay Mesh Repair for Ventral Hernia in Dhaka Medical College Hospital, Dhaka, Bangladesh (Journal of Surgical Sciences, 2025)
Background: The common abdominal hernias include paraumbilical, umbilical, incisional and epigastric hernia. All varieties of ventral hernias are characterized by a defect in anterior abdominal wall. Incisional hernia is defined as a defect occurring through the operative scar. It is the only hernia considered to be truly iatrogenic. It occurs due to failure of the lines of closure of abdominal wall following laparotomy. Conventionally these hernias are treated by suture repair which has led to a substantial rate of recurrence whereby increasing demand for a better technique of repair. The introduction of mesh repair of these hernias has shown encouraging results over the past few years and many studies have shown a substantial decrease in the rate of recurrence with this technique.  Objectives: To assess the early post-operative complications (within 30 days) following Intra peritoneal onlay mesh repair in Dhaka Medical Collage & Hospital, Dhaka, Bangladesh.  Methods: This Observational study conducted in department of Surgery, DMCH, Dhaka in study period from June 2016 to May 2017. A total of 30 patients were purposively selected from department of Surgery in DMCH who underwent laparoscopic Intra peritoneal onlay mesh repair for ventral hernia. Patients with ventral hernia in department of Surgery, DMCH, Dhaka in study period. Data analysis was done by SPSS for windows version 21. The 30 days post-operative outcome was analyzed. Postoperatively, patients were observed for Post-operative pain, seroma, post-operative ileus, post- operative cellulitis, wound infection, mesh infection, mesh migration, early mesh failure. Patients were followed up on 7th, 15th and 30th post-operative day.  Results: With the objectives to determine the early post-operative complications (within 30 days) following Intra peritoneal onlay mesh repair in department of surgery in DMCH, a total of 30 patients were purposively selected. It was found that more than half of the patients (55.3%) were 31-45 years age group. Only 13.8 % from younger age group (15-30 years). Rest of them are older (>46 years) group. Among the respondents most of the patients were female (65.1%). It was found that 36.66 % patient were with incisional hernia (81.6%) followed by para umbilical hernia (11.2%), only 2.6% were umbilical hernia. It also showed that all hernia cases were common after 30 years except umbilical hernia. Most of the cases in this study, hernia lesions were between 5-7 cm in size (73.7%). 13.8% were hernia with size of defect 8 cm and 12.5 % were hernia defect less than 5 cm. Most of the incisional and Para-umbilical lesions were between 5-7 cm sizes whereas epigastric hernia lesions were less than 5 cm size. Among all post-operative complications, seroma formation was highest in this study. In incisional hernia repair 23.38% patients develop seroma after operation, when post- operative seroma formation compared with different type of hernia repair, it found statistically significant in this study. 16% patients with incisional hernia had developed post-operative wound infection.Conclusion: Among the ventral abdominal hernia incisional and the para umbilical hernia constitute the most. In the repair of these hernias through laparoscopic intraperitoneal onlay mesh repair the most common early post-operative complications were seroma formation and wound infection in the form of superficial surgical site infection. Larger hernia required longer operative duration and associated with more post-operative complication.Journal of Surgical Sciences (2021) Vol. 25 (1) : 10-22